In Focus/Health-Stress Test What is the Health Impact on Leaders - McDowell-Larsen, Sharon; McDowell-Larsen, Sharon (Center for Creative Leadership, 2002)
For leaders, stress comes with the territory. The increasingly competitive nature of global business, the pressures to succeed quickly and the fear of failing, the physical demands of late nights and constant traveling, and the increasing difficulty of balancing work with personal and family needs are just some of the things.